2023
DOI: 10.1007/s00170-023-11794-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of diamond-like carbon coatings for drill bits using plasma-enhanced chemical vapor deposition

Abstract: This study demonstrates the performance enhancement of drill bits during dry cutting operation of LM6 aluminum alloy and bright mild steel using optimized Diamond-Like-Carbon (DLC) coatings. DLC coatings are deposited using Plasma Enhanced Chemical Vapour Deposition (PECVD) process by varying the process parameters, bias voltage, bias frequency, gas mixture, and working pressure. DLC coatings were grown over the silicon, high-speed steel, and stainless-steel pin substrate. Coating's chemical, composition, topo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…In addition, it was interesting to observe the surface roughness [36] of the 3D print mold on the surface of the lens using a scanning electron microscope [37] or a 3D optical profilometer [38]. Also, it was interesting to analyze the chemical composition and changes that produced variation in fabrication temperature using Raman spectroscopy [39] or at- This paper presented a conformal heating channel to enhance the temperature uniformity of the mold surface in the LSR injection molding of an optical convex lens. It should be noted that the fabricated LSR injection mold fulfilled sustainable development goals [23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was interesting to observe the surface roughness [36] of the 3D print mold on the surface of the lens using a scanning electron microscope [37] or a 3D optical profilometer [38]. Also, it was interesting to analyze the chemical composition and changes that produced variation in fabrication temperature using Raman spectroscopy [39] or at- This paper presented a conformal heating channel to enhance the temperature uniformity of the mold surface in the LSR injection molding of an optical convex lens. It should be noted that the fabricated LSR injection mold fulfilled sustainable development goals [23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was interesting to observe the surface roughness [35] of the 3D print mold on the surface of the lens using a scanning electron microscope [36] or a 3D optical profilometer [37]. Also, it was interesting to analyze the chemical composition and changes that produced variation in fabrication temperature using Raman spectroscopy [38] or attenuated total reflectance using Fourier-transform infrared spectroscopy [39]. This research is ongoing and the results will be presented in a later work.…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies [11][12][13] have shown that one of the most effective ways to enhance wear resistance and surface hardness is by coating it. Coating technology can be broadly categorised into two groups: one is thermal diffusion type, including gas diffusion infiltration, hot dip coating, packcementation, 13 and high-energy beam surface treatment 14,15 ; the other is deposition type, including physical vapour deposition, [16][17][18][19] chemical vapour deposition, [20][21][22] electroplating, 23,24 spraying, 25,26 micro-arc oxidation, 27,28 etc. Pack-cementation is an efficient, simple, mature, and low-cost approach for preparing metallic and ceramic coatings on metals and alloys.…”
Section: Introductionmentioning
confidence: 99%
“…High-Speed Steel (HSS) drill bits, alloyed with carbon, chromium, molybdenum, tungsten, and vanadium, epitomize heightened hardness, heat resistance, and durability compared to standard steel bits [17]. HSS drill bits excel in drilling materials ranging from cast iron and steel to non-ferrous metals and stainless steel [18], [19]. Polycrystalline Diamond (PCD) drill bits, characterized by diamond particle-infused cutting edges bound by metal, shine in demanding tasks.…”
Section: Introductionmentioning
confidence: 99%